Síntese de ferritas dopadas com cobre a partir da reciclagem de baterias de íon-Li (CuFe2O4-LiBs) e suas aplicações na descoloração do corante azul de metileno pelo processo de foto Fenton heterogêneo e como pseudocapacitor eletroquímico - Rocha, Ana Kelly Simões (2018)
In this study, a co-precipitation method was used for the synthesis of Fe2O3/Fe3O4and CuFe2O4-A from commercial reagents and CuFe2O4-LiB from recycled copper from the current collector of a lithium-ion battery (LiBs). X-ray diffraction identified the tetragonal structure of CuFe2O4-LiB. Scanning electron microscopy and transmission electron microscopy showed agglomerates of spherical nanometric particles. The photocatalytic properties were analyzed by monitoring methylene blue (MB) discoloration in a heterogeneous photo-Fenton process in the presence of solar radiation. The ideal conditions for MBdiscoloration, determined using a factorial design, were 10 mg CuFe2O4, pH7 and 0.3 molL -1and H2O2. The efficiency of the discoloration was 96.1% in 45 minutes of reaction. Analysis of the MBsolution after discoloration showed a reduction of 32.3% in chemical oxygen demand (COD) after 105 minutes of reaction. Ion chromatography detected formic and acetic acids as MBdegradation products and the inductively coupled plasma optical emission spectrometry showed the presence of iron and copper ions in the treated solution (system I) at concentrations acceptable under the legislation. CuFe2O4-LiB has been shown to be an efficient catalyst for discoloration/degradation of MBby heterogeneous photo-Fenton reactions. Cyclic voltammetry was used for the electrochemical characterization of CuFe2O4-LiB electrodes. CuFe2O4-LiB electrodes showed high reversibility, charge efficiency and a specific capacitance of 2.4 F.g-1(10.0 mV.s-1), which are favorable characteristics for pseudocapacitors. This study investigated the multifunctionality of CuFe2O4-LiB as a photocatalyst for the discoloration and degradation of MBdye under solar radiation and as a pseudocapacitor. Therefore, this study is of scientific, economic, environmental and social interest